The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017 IEEE International Conference on Pervasive Computing and Communications Workshops (PerCom Workshops) 2017
DOI: 10.1109/percomw.2017.7917583
|View full text |Cite
|
Sign up to set email alerts
|

A mobile lifelogging platform to measure anxiety and anger during real-life driving

Abstract: Abstract-The experience of negative emotions in everyday life, such as anger and anxiety, can have adverse effects on longterm cardiovascular health. However, objective measurements provided by mobile technology can promote insight into this psychobiological process and promote self-awareness and adaptive coping. It is postulated that the creation of a mobile lifelogging platform can support this approach by continuously recording personal data via mobile/wearable devices and processing this information to mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Previous studies on real-life driving by Dobbins and Fairclough [66] have reported that the area of lifelogging has emerged as an application that is designed to continuously measure personal data with the purpose of supporting recall and self-reflection. Emotions can be captured continuously and in an unobtrusive manner.…”
Section: Emotion Recognition Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on real-life driving by Dobbins and Fairclough [66] have reported that the area of lifelogging has emerged as an application that is designed to continuously measure personal data with the purpose of supporting recall and self-reflection. Emotions can be captured continuously and in an unobtrusive manner.…”
Section: Emotion Recognition Technologiesmentioning
confidence: 99%
“…As we previously mentioned, researchers in the automotive domain [66] have established the need for unobtrusive research. Furthermore, in-situ methods such as the Experience Sampling Method and the Day Reconstruction Method are increasingly applied in longitudinal settings, as Karapanos et al [68] highlighted, while retrospective techniques offer a cost-effective alternative to longitudinal studies.…”
Section: Unobtrusive Long-term Behavioral Researchmentioning
confidence: 99%